Audiovisual Science Communication on TV and YouTube. How Recipients Understand and Evaluate Science Videos - Boy, Bettina; Bucher, Hans-Jürgen; Christ, Katharina (Frontiers in Communication, 2020)
With the emergence of the Internet, social media and video platforms are gaining considerable influence on the traditional media landscape in general and on science communication in particular. This has changed the role of science journalists as gatekeepers because many platforms are based on a participatory culture, in which passive consumers can become active participants. In addition to scientists, non-scientific actors also act as experts and participate in the communication process between science and the public. In contrast to the relevance of YouTube for science communication there is a lack of research focusing on the questions of how internet users receive YouTube videos to acquire information about science, how successful audiovisual media function in knowledge transfer, and what effects it has on the epistemic regime of a society. Therefore, this study combines a discourse analysis with the aim to create a typology of YouTube videos and an audience study for investigating knowledge transfer. In the first step, this article presents the results of a systematic analysis and categorization of 400 German science videos, from which four types of audiovisual science communication on YouTube were derived: presentation films, expert films, animation films, and narrative explanatory films. In order to clarify how powerful these new forms of science communication are in terms of knowledge transfer, attitudes, and trust towards the presentation of science, a discourse analysis of the videos is combined with a multi-level reception study and an online survey. The reception study included eye-tracking to investigate the allocation of attention and two different methods of knowledge tests. The results show that the type of video has an important impact on knowledge transfer and para-social effects. One of the central results of the audience study is that the videos' gaze guidance, the recipients' allocation of attention, and the results of knowledge testing are closely intertwined. The correlation of data from eye-tracking and the two knowledge tests prove in principle that the more homogeneous the gaze patterns of the recipients are, the better they score in the multiple-choice test as well as in the concept mapping test.